A perovskite quantum dot composite material and preparation method thereof, and quantum dot device

The perovskite quantum dot composite material prepared by low-temperature calcination uses the dual methods of inorganic mesoporous material packaging and CQDs doping to solve the problem of insufficient stability of PQDs, and realizes the high stability of the material and the potential for commercial application.

CN115975627BActive Publication Date: 2025-04-15WUXI UTMOST LIGHT TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211618984.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-14
Publication Date
2025-04-15
Estimated Expiration
2042-12-14

AI Technical Summary

Technical Problem

In the prior art, perovskite quantum dots (PQDs) have insufficient stability, especially poor thermal and chemical stability, which is difficult to meet the requirements of commercial applications.

Method used

Perovskite quantum dot composite materials are prepared by mixing and grinding the collapser, inorganic mesoporous material, PQDs precursor and CQDs precursor, and the stability of PQDs is improved by using the dual means of inorganic mesoporous material packaging and CQDs doping.

Benefits of technology

The perovskite quantum dot composite material has a controllable size and simple process, which improves the water, oxygen, light and thermal stability of PQDs, and enhances its potential for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115975627B_ABST
    Figure CN115975627B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of perovskite quantum dots, and specifically relates to a perovskite quantum dot composite material, a preparation method thereof, and a quantum dot device. The preparation method of the perovskite quantum dot composite material provided by the present invention comprises the following steps: mixing an inorganic mesoporous material, a collapse agent, a PQDs precursor, and a CQDs precursor, grinding them uniformly, and calcining them at low temperature to obtain a crude product of a PQDs composite material encapsulated by an inorganic mesoporous material and doped with CQDs, and washing the crude product to remove impurities to obtain a PQDs composite material protected by dual means of encapsulation and doping, and having good water, oxygen, light, and heat stability. This method adopts low-temperature calcination and a one-step method to prepare a size-controllable PQDs composite material, and the process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of perovskite quantum dots, and in particular relates to a perovskite quantum dot composite material and a preparation method thereof, and a quantum dot device. Background Art

[0002] With the rise of quantum dot display technology, people are paying more and more attention to materials with excellent optoelectronic properties. 3 (A=Cs, FA or MA, B=Pb or Sn, X=Cl, Br or I) type perovskite quantum dots (PQDs) stand out due to their unique properties such as strong quantum light emission, narrow emission bandwidth, and adjustable emission wavelength, showing great application prospects. However, the biggest problem in the commercial application of PQDs is stability, which can be divided into two aspects. On the one hand, due to the inherent structural instability of PQDs, their thermal stability is poor; on the other hand, due to the low formation energy of PQDs, their chemical stability is poor and they are easily destroyed by water and oxygen in the air.

[0003] Scientists have made a series of attempts to improve the stability. The existing technology has a method of improving the water and oxygen resistance of PQDs by oxide encapsulation. This method uses high-temperature calcination of mesoporous molecular sieves to collapse and encapsulate PQDs. However, the molecular sieves will collapse and connect with each other under high-temperature calcination, and the size of the composite material cannot be effectively controlled. In addition, due to the problem of too high calcination temperature, it is impossible to stabilize the lattice of PQDs by introducing ligands to improve its resistance to dry heat and blue light. The existing technology also has a solution method for preparing SiO 2 The preparation method of encapsulated carbon quantum dots (CQDs) doped PQDs composite material improves the stability of PQDs by dual means of encapsulation and doping. However, the carboxyl groups of CQDs can only react with organic-inorganic perovskite quantum dots MAPbBr 3 The MA in the PQDs can generate hydrogen bonds to stabilize the PQDs lattice, but cannot generate hydrogen bonds or other effects to stabilize the PQDs lattice with pure inorganic PQDs. Moreover, the hydrogen bond force is weak and cannot effectively stabilize the PQDs lattice. In addition, this method is to hydrolyze ethyl orthosilicate into SiO 2 The carbon quantum dots and PQDs are wrapped to isolate water and oxygen. However, this method is difficult to ensure that SiO 2 Completely encapsulate CQDs and PQDs, and it is impossible to control the hydrolysis of ethyl orthosilicate to SiO 2 The size and thickness of the device are still far from commercial application. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the above-mentioned defects of the method for improving the stability of PQDs in the prior art, thereby providing a perovskite quantum dot composite material and a preparation method thereof, and a quantum dot device.

[0005] To this end, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a perovskite quantum dot composite material, comprising the following steps:

[0007] S1, mixing and grinding the collapse agent, the inorganic mesoporous material, the PQDs precursor and the CQDs precursor to obtain a mixed material;

[0008] Wherein, the collapse agent is at least one of nitrate or metal halide,

[0009] The CQDs precursor contains carboxyl and / or thiol groups, and also contains amino groups;

[0010] S2, calcining the mixed material at 300-350° C. for 10-60 min in an oxygen-free environment, washing, and drying to obtain the perovskite quantum dot composite material.

[0011] Optionally, in step S1, the mass ratio of CQDs precursor to PQDs precursor is 1:1-1:1.5; typically, non-limitingly, the mass ratio of CQDs precursor to PQDs precursor is adjustable, and the selection range is 1:1-1:1.5, for example: 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, preferably 1:1.2.

[0012] And / or, the mass ratio of the inorganic mesoporous material to the collapse agent is (2-8):1;

[0013] And / or, the mass ratio of the inorganic mesoporous material to the PQDs precursor is 5:1-1:5.

[0014] Optionally, the pore size of the inorganic mesoporous material is ≤30nm; Optionally, the pore size of the inorganic mesoporous material is 5-15nm;

[0015] Optionally, the inorganic mesoporous material is a mesoporous molecular sieve, and the mesoporous molecular sieve includes a silicon-based molecular sieve and a non-silicon-based molecular sieve. Typically, but not limiting, the mesoporous molecular sieve is at least one of MCM, ZSM, NaY, and SBA type molecular sieves; the mesoporous molecular sieve is preferably an MCM-41 type molecular sieve.

[0016] Optionally, the CQDs precursor is selected from small molecule monomers such as histidine, threonine, aromatic amino acids, ethylenediaminetetraacetic acid, 1,3-propylenediaminetetraacetic acid, diammonium hydrogen citrate, cysteine, etc., whose carbon chains contain amine, carboxyl and / or thiol groups that can coordinate with PQDs, preferably histidine.

[0017] The CQDs precursor is polymerized under heating conditions to obtain CQDs. The following is an example of histidine. Histidine is pyrolyzed and carbonized in a tube furnace to form CQDs. The reaction equation is shown below. It can be seen from the reaction equation that histidine is pyrolyzed and carbonized at low temperature to prepare a CQD composed of carbon atoms with SP 2 , SP 3 The hybridized hexagonal honeycomb lattice structure is surrounded by a large number of hydroxyl, amino and carboxyl groups, namely CQDs.

[0018]

[0019] Optionally, the nitrate in the collapse agent is KNO 3 、NaNO 3 Mg(NO 3 ) 2 At least one of;

[0020] The metal halide is at least one of KBr and NaBr.

[0021] The collapsing agent is preferably KNO 3 、NaNO 3 and KBr mixture.

[0022] Optionally, the PQDs precursor includes cesium halide and further includes lead halide and / or tin halide.

[0023] Typically, the PQDs precursor can be selected as CsBr+PbBr 2 、CsI+PbI 2 、CsCl+PbCl 2 , preferably CsBr+PbBr 2 ; The molar ratio of Cs:Pb elements in the PQDs precursor is preferably 1:1; the molar ratio of Pb element to halogen is adjustable, preferably 1:1.

[0024] Optionally, in step S1, the collapse agent, the inorganic mesoporous material, the PQDs precursor, and the CQDs precursor are dispersed in water, mixed, evaporated to dryness, and ground.

[0025] Optionally, in step S2, the oxygen-free environment is a nitrogen environment or an inert gas environment;

[0026] and / or, the heating rate during the calcination process is 10-40°C / min;

[0027] Typically, but not limiting, the calcination in step S2 is carried out in a tube furnace, and N is introduced during the heating process. 2 The range of the heating rate can be selected as 10-40℃ / min, for example: 10℃ / min, 15℃ / min, 20℃ / min, 25℃ / min, 30℃ / min, 35℃ / min, 40℃ / min, etc., preferably 20℃ / min; the calcination temperature can be selected in the range of 300-350℃, for example: 300℃, 310℃, 320℃, 330℃, 340℃, 350℃, etc.; the calcination time can be selected in the range of 10-60min, for example: 10min, 20min, 30min, 40min, 50min, 60min, etc., preferably 20min.

[0028] and / or, washing with water;

[0029] And / or, the drying is vacuum drying.

[0030] Optionally, in step S1, the collapse agent, inorganic mesoporous material, PQDs precursor, and CQDs precursor are placed in deionized water, heated, stirred, evaporated, and then ground; the collapse agent, inorganic mesoporous material, PQDs precursor, and CQDs precursor can also be directly mixed and then ground. The former mixing method is preferred. This is because these precursors and collapse agents can be dissolved and dispersed in water, and can enter the molecular sieve pores after evaporation. Although grinding can also bring the raw materials into the molecular sieve pores to a certain extent, it is not as sufficient as the dissolution and dispersion mixing method.

[0031] The present invention also provides a perovskite quantum dot composite material prepared by the above preparation method.

[0032] The present invention also provides a quantum dot device, the above-mentioned perovskite quantum dot composite material.

[0033] Typically and non-limitingly, the perovskite quantum dot composite material provided by the present invention can be used for quantum dot films on LED displays, light-emitting diodes, photodetectors, etc.

[0034] Specifically, taking the inorganic mesoporous material as an example, the preparation process of the overall PQDs composite material can be:

[0035] (1) Take appropriate amounts of collapse agent, molecular sieve, PQDs precursor, and CQDs precursor, mix them, place them in an aqueous solution, mix them by ultrasonication, and evaporate them to dryness at 70°C.

[0036] (2) The evaporated sample is taken out and ground, spread flat in a crucible, and placed in a tube furnace for low-temperature calcination. The collapse agent, PQDs precursor, and CQDs precursor enter the molecular sieve pores through dissolution and then evaporated and calcined at low temperature. The molecular sieve collapses and seals, and the formed CQDs doped PQDs are encapsulated in the pores, isolating the damage of water and oxygen to the PQDs. The carboxyl, amino, and thiol groups on the surface of CQDs form hydrogen bonds with the hydroxyl groups in the molecular sieve pores to fix the position of the CQDs. At the same time, the carboxyl, thiol, and amino groups on the surface of CQDs undergo protonation reactions to produce carboxylate ions, ammonium ions, and thiol anions (-S - ) and PQDs to produce coordination, which plays a passivation role and further fixes and stabilizes the lattice of PQDs. The stability of PQDs is improved by dual means.

[0037] (3) The crude product of the calcined PQDs composite material was cooled at room temperature for 24 h, washed with water, and centrifuged three times to obtain the final product, i.e., a molecular sieve encapsulated CQDs-doped PQDs composite material (e.g., using MCM-41 molecular sieve to encapsulate CQDs-doped CsPbBr 3 , it is named CQDs-CsPbBr 3 @MCM-41, subsequent preparations of composite materials using other types of molecular sieves and other types of PQDs will be named in this way).

[0038] The technical solution of the present invention has the following advantages:

[0039] The preparation method of the perovskite quantum dot composite material provided by the present invention comprises the following steps: mixing an inorganic mesoporous material, a collapse agent, a PQDs precursor, and a CQDs precursor, grinding them uniformly, and calcining them at low temperature to prepare a crude product of a PQDs composite material encapsulated by an inorganic mesoporous material and doped with CQDs, and washing the crude product to remove impurities to obtain a PQDs composite material encapsulated by an inorganic mesoporous material and doped with CQDs. This method adopts low-temperature calcination and a one-step method to prepare a size-controllable PQDs composite material, and the process is simple.

[0040] Compared with the prior art, the present invention avoids the problem of mutual connection between materials and difficult size control caused by high-temperature calcination by introducing a collapse agent and a low-temperature roasting process. The present invention dopes PQDs by selecting CQDs precursors rich in carboxyl and / or thiol groups and amino groups. Carboxyl and / or thiol groups and amino groups form carboxylate ions, ammonium ions and thiol anions at high temperatures, which can form strong chemical bonds with pure inorganic PQDs, play a role in passivating PQDs, and more effectively stabilize the PQDs lattice.

[0041] The PQDs composite material prepared by the method provided by the present invention can not only protect PQDs from water and oxygen corrosion through the inorganic mesoporous material shell, but also improve the lattice stability of PQDs through the chemical bond force between CQDs and PQDs. The PQDs composite material with dual protection means has good water, oxygen, light and heat stability.

[0042] The preparation method of the perovskite quantum dot composite material provided by the present invention can remove impurities by washing with water, and no organic solvent is needed in the whole process, thus avoiding further damage to the environment and saving costs. The low-temperature roasting method avoids the problem of high temperature hazards encountered in the scale-up production, solves the problem of scale-up process difficulties, and provides new ideas for the commercialization process. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0044] Figure 1 is a schematic diagram of the preparation process of the perovskite quantum dot composite material in Example 1 of the present invention;

[0045] Figure 2 is the emission spectrum of the perovskite quantum dot composite material obtained in Example 1 of the present invention under 365nm excitation light;

[0046] Figure 3 is a graph showing the change of PLQY over time of the perovskite quantum dot composite material provided in Example 1 and Comparative Example 1 under 85° C. dry heat aging test;

[0047] Figure 4 It is a graph showing the change of PLQY over time of the perovskite quantum dot composite material provided in Example 1 and Comparative Example 1 under 447nm, 1000nit blue light aging test;

[0048] Figure 5 This is a graph showing the change in PLQY over time of the perovskite quantum dot composite material provided in Example 1 and Comparative Example 1 under a water and oxygen aging test. DETAILED DESCRIPTION

[0049] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0050] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0051] In order to facilitate comparison between data, the sources and some parameters of the mesoporous molecular sieves used in the following examples and comparative examples are as follows:

[0052] MCM-41 molecular sieve comes from Nanjing Xianfeng Nano, with a pore size of 5nm and a specific surface area of ​​≥800m 2 / g.

[0053] ZSM-5 molecular sieve is from Nanjing Xianfeng Nano, with a silicon-aluminum ratio of 38, a pore size of 10nm, and a specific surface area of ​​330-400m 2 / g.

[0054] Example 1

[0055] This embodiment provides a CQDs-CsPbBr 3 The preparation steps and parameters of @MCM-41 composite material are as follows:

[0056] (1) Weigh 0.3 g of CQDs precursor: histidine and set aside. Weigh 0.4 g of MCM-41 molecular sieve and set aside. Weigh the collapse agent: NaNO 3 0.06g, KBr 0.03g, KNO 3 Weigh PQDs precursors: CsBr 0.13 g, PbBr 2 0.21g is reserved.

[0057] (2) The above-mentioned CQDs precursor, MCM-41 molecular sieve, collapse agent and PQDs precursor were placed in 20 ml of deionized water, stirred and evaporated to dryness at 70°C, and the evaporated sample was taken out, ground and spread evenly in a crucible.

[0058] (3) Place the crucible in a tubular furnace and introduce N 2 , in N 2 In the atmosphere, the temperature was raised from 20°C to 320°C at a heating rate of 20°C / min, and then kept at 320°C for 20 min. After taking out the sample, it was cooled at room temperature for 24 h to obtain CQDs-CsPbBr 3@MCM-41 composite material crude product.

[0059] (4) CQDs-CsPbBr 3 The crude product of @MCM-41 composite material was washed three times with deionized water, and the product was centrifuged and placed in a vacuum drying oven at 60°C for 24 hours to obtain the purified CQDs-CsPbBr 3 @MCM-41 composite material.

[0060] Figure 2 CQDs-CsPbBr under 365nm excitation light 3 @The emission peak spectrum of MCM-41 composite material in aqueous solution shows that the maximum emission intensity peak is located at 530nm, and the PLQY (photoluminescence efficiency) is as high as 90.2%.

[0061] Example 2

[0062] This embodiment provides a CQDs-CsPbBr 3 @The preparation of the ZSM-5 composite material is different from that in Example 1 in that the molecular sieve MCM-41 is replaced by the molecular sieve ZSM-5.

[0063] Example 3

[0064] This embodiment provides a CQDs-CsPbBr 3 @The preparation of the MCM-41 composite material is different from that of Example 1 in that the calcination temperature is 350°C.

[0065] Example 4

[0066] This embodiment provides a CQDs-CsPbBr 3 @The preparation of the MCM-41 composite material is different from that of Example 1, except that the calcination time is 40 min.

[0067] Example 5

[0068] This embodiment provides a CQDs-CsPbI 3 The preparation of the @MCM-41 composite material is different from that in Example 1 in that the PQDs precursors are CsI0.16g, PbI 2 0.28g.

[0069] Example 6

[0070] This embodiment provides a CQDs-CsPbI 3 @The preparation of the ZSM-5 composite material is different from that of Example 5 in that the molecular sieve MCM-41 is replaced by the molecular sieve ZSM-5.

[0071] Example 7

[0072] This embodiment provides a CQDs-CsPbI 3 @The preparation of the MCM-41 composite material is different from that of Example 5 in that the calcination temperature is 350°C.

[0073] Example 8

[0074] This embodiment provides a CQDs-CsPbI 3 @The preparation of the MCM-41 composite material is different from that of Example 5, except that the calcination time is 40 min.

[0075] Example 9

[0076] This embodiment provides a CQDs-CsPbBr 3 @The preparation of the MCM-41 composite material is different from that of Example 1 in that the CQDs precursor is threonine.

[0077] Example 10

[0078] This embodiment provides a CQDs-CsPbBr 3 @The preparation of the MCM-41 composite material is different from that of Example 1 in that the CQDs precursor is cysteine.

[0079] Embodiment 11

[0080] This embodiment provides a CQDs-CsPbBrI 2 @MCM-41 composite material preparation, compared with Example 1, the difference is that the PQDs precursor is CsBr0.13g, PbI 2 0.28g.

[0081] Example 12

[0082] This embodiment provides a CQDs-CsPbBr 3 @MCM-41 composite material preparation, compared with Example 1, the difference is that the collapse agent is NaNO 3 0.07g, KNO 3 0.08g.

[0083] Comparative Example 1

[0084] This comparative example provides a CsPbBr 3 The preparation of the @MCM-41 composite material is different from that of Example 1 in that the raw materials do not include the CQDs precursor histidine.

[0085] Comparative Example 2

[0086] This comparative example provides a CsPbBr3 @The preparation of the ZSM composite material is different from that in Example 1, the molecular sieve MCM-41 is replaced by the molecular sieve ZSM-5, and no CQDs precursor is added.

[0087] Comparative Example 3

[0088] This comparative example provides a CsPbBr 3 The preparation of the @MCM-41 composite material is different from that of Example 1 in that sucrose is used instead of the CQDs precursor histidine.

[0089] Comparative Example 4

[0090] This comparative example provides a CQDs-CsPbBr 3 The preparation of the @MCM-41 composite material is different from that of Example 1 in that the raw materials do not include a collapse agent.

[0091] Comparative Example 5

[0092] This comparative example provides a CQDs-CsPbBr 3 The preparation of the @MCM-41 composite material is different from that of Example 1 in that the raw materials do not include a collapse agent and the calcination temperature is 750°C.

[0093] Performance Testing

[0094] The PQDs composite materials prepared in the embodiments of the present invention and the comparative examples were tested for the time it takes for the PLQY to decrease by 10% under a dry heat aging test, the time it takes for the PLQY to decrease by 10% under a blue light aging test, and their water and oxygen stability. The water and oxygen stability test and the luminescent color under ultraviolet light were observed.

[0095] The specific test method of the dry heat aging test is: placing the prepared and purified perovskite quantum dot composite material in a vacuum drying oven at 85°C, and testing its photoluminescence efficiency at regular intervals.

[0096] The specific test method of the blue light aging test is: place the prepared and purified perovskite quantum dot composite material on a 447nm, 1000nit blue light panel, and test its photoluminescence efficiency regularly.

[0097] The specific test method for water-oxygen stability is: placing the prepared and purified perovskite quantum dot composite material in an aqueous solution and regularly testing its photoluminescence efficiency.

[0098] The specific testing method for product size is: use the dynamic light scattering instrument Dynapro Titan TC to test the size of the purified perovskite quantum dot composite material.

[0099] in, Figure 3The CQDs-CsPbBr prepared in Example 1 3 @MCM-41 composite material and CsPbBr prepared in Comparative Example 1 3 @The PLQY variation of MCM-41 composite material with time under 85℃ dry heat aging test, Figure 4 The CQDs-CsPbBr prepared in Example 1 3 @MCM-41 composite material and CsPbBr prepared in Comparative Example 1 3 @The PLQY of MCM-41 composite material changes with time under 447nm, 1000nit blue light aging test. Figure 5 The CQDs-CsPbBr prepared in Example 1 3 @MCM-41 composite material and CsPbBr prepared in Comparative Example 1 3 @The PLQY variation of MCM-41 composite material with time under water and oxygen aging test.

[0100] Depend on Figure 5 It can be seen that with the addition of molecular sieve collapse agent, the molecular sieve can be sealed at 320 ° C, encapsulating PQDs in the pores and protecting PQDs, that is, isolating the damage of water and oxygen to PQDs; Figure 3 , Figure 4 It can be seen that with the addition of histidine, the precursor of CQDs, the dry heat aging and blue light aging resistance of PQDs are improved, indicating that the addition of histidine improves the dry heat and blue light resistance of PQDs. The reason for this phenomenon is that histidine is thermally decomposed to form CQDs rich in carboxyl and amino groups. The carboxyl and amino groups around CQDs undergo protonation reaction at high temperature to form carboxylate ions and ammonium ions. Through coordination, they can form strong chemical bonds with PQDs, passivate the defects on the surface of PQDs, reduce its surface energy, improve the lattice stability of PQDs, inhibit its phase change, and thus improve the dry heat resistance and blue light stability of PQDs.

[0101] The specific test results of each embodiment and comparative example are shown in the table below.

[0102] Table 1

[0103]

[0104] From the data in the above table, it can be seen that compared with Example 2, and compared with Example 5 and Example 6, the replacement of molecular sieves with different pore sizes and types has an impact on their blue light and dry heat performance. This may be because the molecular sieve pores become larger. After the molecular sieve pores collapse, PQDs and CQDs cannot completely fill the pores, resulting in a decrease in their stability, but they all have good water-oxygen stability, indicating that different types of molecular sieves can protect the water-oxygen stability of PQDs; compared with Example 1 and Example 3 and Example 4, Example 5 and Example 7 and Example 8, it is shown that extending the calcination time and increasing the calcination temperature will reduce the stability to a certain extent. The reason for this phenomenon may be that the calcination temperature is too high and the calcination time is extended, the carbonization degree of CQDs is deepened, the number of functional groups such as carboxyl, amino and hydroxyl groups around CQDs is reduced, and the coordination passivation effect on PDQs is weakened.

[0105] Comparison between Example 1, Example 9, Example 10 and Comparative Example 3 shows that the material of the CQDs precursor (whether it has a group that can coordinate with PQDs) has a great influence on the dry heat and blue light stability of PQDs. If the material of the CQDs precursor has a group that can passivate PQDs, it can stabilize the lattice of PQDs and improve the stability of PQDs.

[0106] Comparison between Example 1 and Example 6 and Comparative Example 1 and Comparative Example 2 shows that adding a CQDs precursor (a small molecule monomer having a coordination group with PQDs) can improve the lattice stability of PQDs and protect the stability of PQDs by dual means.

[0107] Compared with Example 5 and Example 11, Example 1 has a different PQDs precursor, but the stability is improved, indicating that the present invention can be applied to different types of inorganic perovskite quantum dots; compared with Example 12, Example 1 has a different collapse agent, indicating that the addition of collapse agents in different amounts and types affects the stability of PQDs to a certain extent. This may be because different amounts and types of collapse agents affect the degree of collapse of the molecular sieve. The addition of less collapse agent will cause incomplete sealing of the molecular sieve, thereby causing a decrease in stability; compared with Comparative Example 4, Example 1 does not use a collapse agent, which will cause the molecular sieve to fail to collapse and seal during the calcination process, and fail to isolate water and oxygen, thereby causing unstable water and oxygen stability; compared with Comparative Example 5, Example 1 does not use a collapse agent, and high-temperature calcination will cause the perovskite quantum dot composite material to be too large and uncontrollable, and the CQDs are severely carbonized, and cannot play a role in passivating PQDs.

[0108] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. A method for preparing a perovskite quantum dot composite material, characterized in that: The steps include: S1, mixing and grinding the collapse agent, the inorganic mesoporous material, the PQDs precursor and the CQDs precursor to obtain a mixed material; Wherein, the collapse agent is at least one of nitrate or metal halide, the nitrate is at least one of KNO3, NaNO3, Mg(NO3)2; the metal halide is at least one of KBr and NaBr; The pore size of the inorganic mesoporous material is ≤30nm, and the inorganic mesoporous material is a mesoporous molecular sieve; The CQDs precursor contains carboxyl and / or thiol groups, and also contains amino groups; S2, calcining the mixed material at 300-350° C. for 10-60 min in an oxygen-free environment, washing, and drying to obtain the perovskite quantum dot composite material.

2. The method for preparing the perovskite quantum dot composite material according to claim 1, characterized in that: In step S1, the mass ratio of CQDs precursor to PQDs precursor is 1:1-1:1.5; And / or, the mass ratio of the inorganic mesoporous material to the collapse agent is (2-8):1; And / or, the mass ratio of the inorganic mesoporous material to the PQDs precursor is 5:1-1:

5.

3. The method for preparing the perovskite quantum dot composite material according to claim 1 or 2, characterized in that: The pore size of the inorganic mesoporous material is 5-15 nm; And / or, the mesoporous molecular sieve is at least one of MCM, ZSM, NaY, and SBA molecular sieves.

4. The method for preparing the perovskite quantum dot composite material according to claim 1 or 2, characterized in that: The CQDs precursor is selected from at least one of histidine, threonine, aromatic amino acids, cysteine, ethylenediaminetetraacetic acid, 1,3-propylenediaminetetraacetic acid, and diammonium hydrogen citrate.

5. The method for preparing the perovskite quantum dot composite material according to claim 1 or 2, characterized in that: The PQDs precursor includes cesium halide and further includes lead halide and / or tin halide.

6. The method for preparing the perovskite quantum dot composite material according to claim 1 or 2, characterized in that: In step S1, the collapse agent, the inorganic mesoporous material, the PQDs precursor, and the CQDs precursor are dispersed in water, mixed, evaporated to dryness, and ground.

7. The method for preparing the perovskite quantum dot composite material according to claim 1 or 2, characterized in that: In step S2, the oxygen-free environment is a nitrogen environment or an inert gas environment; And / or, the heating rate during the calcination process is 10-40°C / min and / or, washing with water; And / or, the drying is vacuum drying.

8. A perovskite quantum dot composite material prepared by the preparation method according to any one of claims 1 to 7.

9. A quantum dot device, characterized in that: Includes the perovskite quantum dot composite material as described in claim 8.

Citation Information

Patent Citations

  • Method for preparing fluorescent carbon dots by pyrolyzing ammonium carboxylate

    CN105838364A

  • Preparation method of water-soluble carbon-dot modified perovskite type catalytic material

    CN109772465A